Prevalence and Factors Affecting the Labor Experience: A Systematic Review - Nur Hidayatin; Esti Yunitasari; Iqlima Dwi Kurnia (Pediomaternal Nursing Journal, 2021)
Introduction: Labor experiences have potential short and long term physical and psychological effects on women’s lives. Many factors influenced role in a mother’s experience of childbirth, both positively and negatively. This study aimed to determine the prevalence and factors that influence the delivery experience.Methods: This study searched for articles in the databases, namely Pub Med, Scopus, ProQuest, ScienceDirect, and Sage. The keyword used is labor experience. A total of 3654 articles were found, after selecting studies using PRISMA found 18 corresponding articles.Results: In this study, 18 studies were included in this systematic review, eight studies examined the prevalence of labor experiences. The prevalence of labor experience was 6.8-44%. Factors related to childbirth experiences included: individuals, such as age, parity, fear, self-efficacy, participation, control, expectations, preparation, and interpersonal, such as husband support, caregiver support, unwanted medical problems, such as prolonged labor, stimulation, and induction, forceps delivery, emergency cesarean section, and use of analgesics in mothers, low APGAR scores and transfer to the NICU.Conclusion: This review showed the various factors associated with the childbirth experience. This finding suggests conducting further research into the reason these factors influence the experience of labor.